2019
DOI: 10.1128/iai.00329-19
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17 Receptor E (IL-17RE) and IL-17C Mediate the Recruitment of Neutrophils during Acute Streptococcus pneumoniae Pneumonia

Abstract: Neutrophils contribute to lung injury in acute pneumococcal pneumonia. The interleukin 17 receptor E (IL-17RE) is the functional receptor for the epithelial-derived cytokine IL-17C, which is known to mediate innate immune functions. The aim of this study was to investigate the contribution of IL-17RE/IL-17C to pulmonary inflammation in a mouse model of acute Streptococcus pneumoniae pneumonia. Numbers of neutrophils and the expression levels of the cytokine granulocyte colony-stimulating factor (G-CSF) and tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…IL-17C is a member of the IL-17 cytokine family produced by epithelial cells, and is induced in response to bacterial (Ramirez-Carrozzi et al, 2011;Song et al, 2011;Pfeifer et al, 2013;Roth et al, 2014;Wolf et al, 2016;Steck et al, 2019;Jeon et al, 2020), viral (Ioannidis et al, 2012;Peng et al, 2017), or fungal infections (Conti et al, 2015;Huang et al, 2016). In the lung, several studies have shown that bacteria can induce IL-17C in cell culture systems and in animal models (Ramirez-Carrozzi et al, 2011;Pfeifer et al, 2013;Wolf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17C is a member of the IL-17 cytokine family produced by epithelial cells, and is induced in response to bacterial (Ramirez-Carrozzi et al, 2011;Song et al, 2011;Pfeifer et al, 2013;Roth et al, 2014;Wolf et al, 2016;Steck et al, 2019;Jeon et al, 2020), viral (Ioannidis et al, 2012;Peng et al, 2017), or fungal infections (Conti et al, 2015;Huang et al, 2016). In the lung, several studies have shown that bacteria can induce IL-17C in cell culture systems and in animal models (Ramirez-Carrozzi et al, 2011;Pfeifer et al, 2013;Wolf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression studies have found IL-17RE to be primarily located on epithelial cells in mucosal tissues including the lung, trachea, mouth, stomach, and colon (Li et al, 2006;Ramirez-Carrozzi et al, 2011). Previous studies in murine and in vitro models have shown that IL-17C acts on the epithelium in an autocrine/paracrine manner to induce CXCL1 release and neutrophil recruitment (Wolf et al, 2016;Jamieson et al, 2019;Steck et al, 2019). But this has not yet been examined in highly differentiated HBE.…”
Section: Introductionmentioning
confidence: 99%
“…The IL-17 receptor family consists of five receptor subtypes (IL-17RA to IL-RE), which interact with different members of the IL-17 cytokine family (Il-17A to F) [7,8]. IL-17C is suggested to signal through a complex of IL-17RE and IL-17RA, whereas IL-17RA is also forming a heterodimeric receptor complex with IL-17RC for IL-17A signaling [8]. IL-17RE is primarily expressed by epithelial cells and lymphocytes, such a Th17 cells, whereas IL-17RA is ubiquitously expressed [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…There is a functional overlap between IL-17A and IL-17C. Both cytokines mediate the expression of cytokines, chemokines, and antimicrobial peptides [8]. However, IL-17A is expressed by immune cells (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation